(untitled) (Research, Society and Development, 2021)
The article presents the profile of the city of Campina Grande, Brazil, from the perspective of the Space Syntax of the Theory of Social Logic of Space. In the methodology adopted, we used the model that starts from the Road Centre Line (RCL) map elaboration, which served as a basis for obtaining the Angular Segment Analysis, via Depthmapand QGIS software, generating the syntactic measures presented in the results. The objectives proposed in this study were achieved, for the results show that in the city there are spaces with organic and planned characteristics, which reflect socio-cultural aspects of occupation and settlement of the area along its predominantly heterogeneous formation. As for the urban form, there is a configuration composed of an integrating nucleus, located in the urban center; as for the scores presented, there are average values of NAIN (1.007), NACH (0.911) and INCH (12,213) measures, in which 48% with 40%, 54% and 48%, respectively, of the neighborhoods with average scores higher than the index presented by the city’s configurational analysis. Most of the territory presents values above the average values for the city and for the Brazilian territory. Thus, it is concluded that the central regions seem to present, according to the data obtained, a more favorable configuration for mobility and accessibility, having in the peripheral neighborhoods segregationist aspects that can explain the restriction of movement of individuals regarding the access of goods and services in the city.